A Via Pulchritudinis, e a nova evangelização na América Latina - Santoro, Filippo (Revista eclesiástica brasileira, 2006)
Don Filippo Santoro, Bishop of Petrópolis, State of Rio de Janeiro, demonstrates the fecundity of the pulchritudinous way (the road to God through Beauty) in Theology and its relevance for the task of the new evangelization in Latin America. Reviewing what the Holy Scripture says about the subject, he reminds us of the Theology of Beauty in H.U. Von Balthasar and in the teachings of both Paul the 6th and John Paul the 2nd. In the final part of the study, the author proposes some answers for the challenges faced by the new evangelization in Latin America and specifically in Brazil. “It is paramount”– says Don Filippo –“that Christ’s announcement, Beauty made flesh, be an existential proposition in which we may perceive the possibility of a fully realized life.